HARVEST TIME EFFECT ON QUANTITATIVEANDQUALITATIVE PARAMETERS OF FORAGE MAIZE - V. Mandić1; Z. Bijelić; V. Krnjaja; S. Đorđević; M. Brankov; N. Mićić; A. Stanojković (Journal of Animal and Plant Sciences, 2020)
Maize silage is source of palatable and high-energy forage for ruminants. Therefore, production of high quality forage maize represents an essential strategy for stable production of milk and meat on livestock farms. This study examined the effect of harvest date (early dent, at half milk line, at three quarters milk line and black layer) on the quantitative and qualitative parameters of whole maize plant under contrasting climatic conditions in the Srem - Serbia. A 2 × 4 factorial (two years and the four cutting times) randomized blocks design was used, with three replications. The plant height, stem diameter, number of leaves per plant, forage yield, dry matter yield and dry matter content were higher in 2014 probably due to favorable weather conditions. With the delay of the harvest the forage yield, crude protein content, acid detergent fiber (ADF) and neutral detergent fiber (NDF) decreased, and dry matter yield, dry matter content and ear percentage increased. Sufficiently high dry matter content and ear percentage were achieved at the third harvest. However, the delay of harvested time reduces the quality parameters of the biomass, but this loss in the entire plant is moderated by grain filling.
Keywords: maize; harvest time; forage yield; forage quality